Analysis and Risk Assessment of Seaweed. (17th September 2019) - ,; Sá Monteiro, M; Sloth, J; Holdt, S; Hansen, M
Abstract: During the last decade, the interest on the use of seaweed as food or feed, which was before limited to certain European regional subpopulations, has experienced a significant increase in other regions of the EU. In fact, the growing awareness and interest on sustainable and alternative food sources, healthier lifestyles and changes on dietary patterns brought seaweed to the spotlight for the general worldwide cuisine. Due to their high biosorption and accumulation capacity, seaweed can be an important source of increased exposure to persistent and potential harmful elements, such as cadmium (Cd), lead (Pb), mercury (Hg) and inorganic arsenic (iAs), or even some micronutrients, particularly iodine (I), to which an antioxidant role as been described in seaweed. This concentration potential has raised the interest of several Food Authorities regarding the risk of increased exposure to these elements. Moreover, the European Commission requested the collection of monitoring data on their levels aiming to aid the performance of better risk assessments and potentially set maximum levels on the European Legislation. This work aimed to obtain levels of these elements in species of seaweed ( Fucus vesiculosus, Fucus serratus, Fucus spiralis, Fucus evanescens, Saccharina latissima, ulva lactuca and Ccladophora sp.) cultivated and harvested in Denmark, following European Commission's request. Additionally, a collaboration between Denmark, Ireland, France and the Netherlands was initiated to review and collect all the data available on scientific papers regarding the levels of these contaminants in seaweed worldwide. The final result of this work would be the publication of a review article. This Fellowship also provided on‐the‐job training on the evaluation of applications of new biocides and participation in the science based advises given to the Danish Food and Veterinary Administration, Danish EPA, the Danish Medical Agency and ECHA.